Japan, NAFTA and Europe
XVII, 248 p.
Keywords: Emerging trade blocs in North America and the European Community are transforming the global economy and Japan's place in it. Will trade blocs be trade diverting or create new opportunities for Japanese trade and investment? Will a new Asian-Pacific trade bloc emerge in response to this new challenge? How will the collapse of the Soviet empire and the emergence of China as an economic power affect Japan's approach to trade blocs in its two most lucrative markets?